Insulating film and preparation method thereof, enameled wire, motor and vehicle
By using polyimide and polylactic acid blocks in the enameled insulating film to form a porous structure and combining fluorine groups, the demand for low dielectric constant of high voltage rated motors is solved, and the insulation performance and local discharge starting voltage are improved. Suitable for high voltage motors.
Patent Information
- Application Number
- CN202411059956.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-02
AI Technical Summary
The existing enameled wire insulating film is difficult to meet the requirements of high-rated voltage motors for low dielectric constants, resulting in insufficient local discharge starting voltage, affecting the insulation performance and stability of the motor.
Using block polymer insulating films, including polyimide and polylactic acid blocks, forms a porous structure by degradation, uses the low dielectric constant of air to reduce the dielectric constant of the insulating film, and combines fluorine groups to further optimize the dielectric. performance, while improving mechanical and thermal properties.
It realizes the low dielectric constant, excellent mechanical and thermal performance of the insulating film, improves the starting voltage value of the local discharge, avoids the local discharge phenomenon, extends the service life of the motor, and is suitable for high-voltage motors not less than 800V.
Smart Images

Figure BDA0004978565870000051 
Figure BDA0004978565870000141 
Figure HDA0004978565950000011
Abstract
Description
Technical Field
[0001] The present application relates to the field of enameled wires, and in particular, to an insulating film and a preparation method thereof, an enameled wire, a motor, and a vehicle. Background Art
[0002] With the rapid development of the global economy and the motor industry, the demand for high-rated voltage motors (referred to as "high-voltage motors") is increasing. As the main conductive material inside the motor, enameled wire is responsible for transmitting current to the stator and rotor windings of the motor. Enameled wire includes conductive material and an insulating film coated on its surface. In order to meet the performance requirements of high-rated voltage motors, the partial discharge inception voltage (PDIV) value of the enameled wire can be increased, that is, the PDIV value of the enameled wire can be made higher than the overshoot voltage during motor operation to ensure that insulation loss does not occur due to partial discharge. Since the dielectric constant is correlated with the PDIV value, the lower the dielectric constant, the higher the PDIV value. However, the current enameled wire insulation film is difficult to meet the requirements of high-rated voltage motors for low dielectric constants, and still needs to be studied. Summary of the invention
[0003] In view of the technical problems existing in the background technology, the present application provides an insulating film and a preparation method thereof, an enameled wire, a motor and a vehicle. The insulating film of the present application has excellent low dielectric properties, and at the same time has excellent mechanical and thermal properties, which helps to improve the performance of the motor and can be used for high-voltage motors of not less than 800V.
[0004] In a first aspect, the present application provides an insulating film, which includes a block polymer, wherein the block polymer includes: a polyimide block and a polylactic acid block; and the insulating film has a porous structure.
[0005] The present application at least includes the following beneficial effects: the insulating film of the present application contains a block polymer formed by polyimide and polylactic acid. Since polylactic acid has good biodegradability, it can be degraded in the air to produce CO2, thereby forming a porous structure. The porous structure can be connected to the air, and since the dielectric constant of air is the lowest (close to 1), the dielectric constant of the insulating film is further reduced, thereby better meeting the requirements of high-voltage motors.
[0006] In some embodiments, the porosity of the porous structure is 20% to 80%.
[0007] In some embodiments, the polyimide block is generated by reacting at least a dianhydride monomer and a diamine monomer.
[0008] In some embodiments, the diamine monomer has a hydroxyl group, and the hydroxyl group can undergo an esterification reaction with a carboxyl group in the polylactic acid block.
[0009] In some embodiments, the dianhydride monomer further has a fluorine group;
[0010] And / or, the dianhydride monomer includes at least one of hexafluoroisopropylphthalic anhydride, 9,9-bis(trifluoromethyl)-2,3,6,7-oxanthene tetracarboxylic dianhydride, 1,4-bis(3,4-dicarboxytrifluorophenoxy)tetrafluorophthalic anhydride, 1,4-bis(trifluoromethyl)-2,3,5,6-benzenetetracarboxylic dianhydride, 1,4-difluoropyromellitic dianhydride, and 2,2-bis[4-(3,4-dicarboxytrifluorophenoxy)phenyl]hexafluoropropane dianhydride;
[0011] And / or, the diamine monomer includes at least one of 3,3'-dihydroxybenzidine, 4,6-diaminoresorcinol dihydrochloride and 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane.
[0012] In some embodiments, the number average molecular weight of the polyimide block is 105,000 to 200,000;
[0013] And / or, the number average molecular weight of the polylactic acid block is 50,000 to 120,000.
[0014] In some embodiments, the insulating film satisfies at least one of the following conditions:
[0015] Under an electromagnetic wave with a frequency of 1 kHz, the dielectric constant of the insulating film is 2.01 to 2.28, and the dielectric loss factor is 0.001 to 0.006;
[0016] The tensile strength of the insulating film is 180MPa to 222MPa;
[0017] The elongation at break of the insulating film is 190.4% to 211.2%;
[0018] The thermal expansion coefficient of the insulating film is 60.02 ppm / °C to 71.23 ppm / °C.
[0019] A second aspect of the present application provides a method for preparing an insulating film, the method comprising:
[0020] Degrading the insulating base film to obtain the insulating film having a porous structure;
[0021] The insulating base film includes a second block polymer, the second block polymer includes the polyimide block and the polylactic acid block, and the content of the polylactic acid block in the insulating base film is greater than the content of the polylactic acid block in the insulating film.
[0022] In some embodiments, the molar ratio of the polyimide block to the polylactic acid block in the second block polymer is 1:(2-2.5).
[0023] In some embodiments, the method of preparing the second block polymer comprises:
[0024] The diamine monomer and the dianhydride monomer are polymerized in an organic solvent to obtain a polymerization slurry;
[0025] Esterifying the polymerized slurry with polylactic acid to obtain an esterified product;
[0026] The esterification product is subjected to imidization treatment to obtain the second block polymer.
[0027] In some embodiments, the organic solvent includes: at least one of N,N-dimethylacetamide, N-methylpyrrolidone, m-cresol, and 1,4-butyrolactone;
[0028] And / or, the polymerization treatment temperature is 25°C to 30°C;
[0029] And / or, the polymerization treatment time is 8h to 10h;
[0030] And / or, the viscosity of the polymerization slurry is 90,000 cps to 110,000 cps.
[0031] In some embodiments, the esterification process comprises:
[0032] The polymerization slurry, the catalyst and the slurry containing polylactic acid are mixed to obtain a mixed solution;
[0033] Dropping a dehydrating agent solution into the mixed solution to perform an activation reaction to obtain an activated solution;
[0034] The activation solution is subjected to an esterification reaction to obtain the esterification product.
[0035] In some embodiments, the catalyst includes one or more of 4-dimethylaminopyridine, pyridine, triethylamine, and N-methylpiperidine;
[0036] And / or, the dehydrating agent comprises: one or more of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N,N-dicyclohexylcarbodiimide;
[0037] And / or, the solvent contained in the dehydrating agent solution includes: one or more of N,N-dimethylacetamide, N-methylpyrrolidone, m-cresol, and 1,4-butyrolactone;
[0038] And / or, the temperature of the activation reaction is -2°C to 2°C;
[0039] And / or, the activation reaction time is 20min to 40min;
[0040] And / or, the temperature of the esterification reaction is 25°C to 30°C;
[0041] And / or, the esterification reaction time is 8h to 15h.
[0042] In some embodiments, the imidization treatment includes: 70° C. to 90° C. for 40 min to 60 min, 150° C. to 170° C. for 20 min to 40 min, and 240° C. to 260° C. for 20 min to 40 min.
[0043] In some embodiments, the degradation treatment includes placing the insulating base film at a temperature of 20° C. to 30° C. for 10 d to 30 d.
[0044] A third aspect of the present application provides an enameled wire, comprising: a conductor; and the insulating film described in the first aspect of the present application, wherein the insulating film covers the outer circumferential surface of the conductor.
[0045] The fourth aspect of the present application provides a motor, which includes: the enameled wire described in the third aspect of the present application.
[0046] In some embodiments, the rated voltage of the motor is not less than 800V.
[0047] The fifth aspect of the present application proposes a vehicle, which includes: the motor described in the fourth aspect of the present application.
[0048] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0050] Figure 1 A schematic flow chart of a method for preparing a block prepolymer film according to one embodiment of the present application is shown;
[0051] Figure 2 A schematic diagram of an esterification process according to an embodiment of the present application is shown. Specific embodiments
[0052] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.
[0053] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0054] In a first aspect, the present application provides an insulating film, which includes a block polymer, wherein the block polymer includes: a polyimide block and a polylactic acid block; and the insulating film has a porous structure.
[0055] Polyimide has high thermal stability and can maintain its physical and chemical properties at high temperatures. Its decomposition temperature is usually above 400°C, and it will not oxidize or degrade at high temperatures. This property makes it extremely suitable for applications where high-temperature operation is required. In addition, polyimide has excellent mechanical strength and toughness, and its tensile strength, bending strength, and impact strength are all high. Polyimide is also an excellent electrical insulation material with excellent electrical insulation properties, which can remain stable under high temperature and high pressure environments.
[0056] The existing polyimide used as the enameled wire insulation film of the motor has the characteristic of low dielectric constant, but its dielectric constant is about 3.4, which is difficult to meet the requirements of high-voltage motors for low dielectric constant.
[0057] In order to achieve a lower dielectric constant and excellent mechanical and thermal properties, the present application attempts to form a porous structure by introducing a polymer that is degradable, and utilizes the characteristics that these porous structures can be connected to air and the dielectric constant of air is the lowest (close to 1), so as to further reduce the dielectric constant. Polylactic acid (PLA) has good biocompatibility and biodegradability. PLA is degraded under the action of air and microorganisms, and the CO2 produced during the degradation process can form a porous structure, which can be connected to air, further reducing the dielectric constant of the insulating film. Thus, the insulating film of the present application is made to have a relatively excellent dielectric constant while having better mechanical properties. In addition, the final product of polylactic acid degradation is water and carbon dioxide, without secondary pollution. Moreover, by introducing polylactic acid to form a block polymer, the processing temperature, glossiness, and air permeability of the insulating film can be further improved, and various common plastic processing methods can be used for production in the later stage, which is more convenient.
[0058] In some embodiments, the porosity of the porous structure is 20% to 80%. For example, the porosity of the porous structure is 20%, 40%, 50%, 60%, 80%, etc. The porosity of the porous structure meets the given conditions, the dielectric constant can be further reduced, and the insulation and voltage resistance are strong and it is not easy to be damaged.
[0059] It should be noted that: pores are the distance between particles of a material, and "porosity" refers to the percentage of the pore volume in a material to the total volume of the material in its natural state. Specifically, the porosity test method for porous structures is: using the solvent immersion method to test, first weigh the weight m of the insulating film, and calculate the volume of the film based on the density of the polymer, recorded as V1; the insulating film is placed in 10mL of deionized water at room temperature for 30 minutes and then taken out, and the volume of the remaining water is measured. The reduced water volume is recorded as V2, and the porosity / % = V2×100% / (V1+V2).
[0060] In some embodiments, the polyimide block is generated by reacting at least a dianhydride monomer and a diamine monomer.
[0061] In some embodiments, the diamine monomer has a hydroxyl group, and the hydroxyl group can undergo an esterification reaction with a carboxyl group in the polylactic acid block.
[0062] In some embodiments, the dianhydride monomer further has a fluorine group. Since fluorine has a strong electronegativity, the introduction of fluorine can further reduce the dielectric constant of the insulating film and improve the dielectric properties.
[0063] In some embodiments, the fluorine-containing dianhydride monomer includes at least one of hexafluoroisopropylphthalic anhydride (6FDA), 9,9-bis(trifluoromethyl)-2,3,6,7-oxanthene tetracarboxylic dianhydride (6FCDA), 1,4-bis(3,4-dicarboxy trifluorophenoxy) tetrafluorophthalic anhydride (10FEDA), 1,4-bis(trifluoromethyl)-2,3,5,6-benzene tetracarboxylic dianhydride (P6FDA), 1,4-difluoropyromellitic dianhydride (PF2DA), and 2,2-bis[4-(3,4-dicarboxy trifluorophenoxy) phenyl]hexafluoropropane dianhydride (BFDA), preferably 6FDA and / or 6FCDA. Since fluorine is a strongly electronegative substance, introducing it into the material will further reduce the dielectric constant of the material.
[0064] In some embodiments, the diamine monomer includes at least one of 3,3'-dihydroxybenzidine, 4,6-diaminoresorcinol dihydrochloride, and 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane.
[0065] Taking the diamine monomer as 3,3' dihydroxybenzidine as an example, the block polymer has a structure shown in the following formula:
[0066]
[0067] m, n, and p are integers of 1 to 100, respectively, wherein Ar represents an aromatic group derived from a dianhydride monomer.
[0068] The insulating film contains a block polymer with the above structure, which has low dielectric constant and excellent mechanical and thermal properties.
[0069] In some embodiments, the number average molecular weight of the polyimide block is 105000 to 200000. For example, the number average molecular weight of the polyimide block is 105000, 110000, 120000, 140000, 150000, 160000, 180000, 200000. The number average molecular weight of the polyimide block meets the given conditions, which can form a suitable amount of porous structure, reduce the dielectric constant, and improve the mechanical and thermal properties.
[0070] In some embodiments, the number average molecular weight of the polylactic acid block is 50000 to 120000. For example, the number average molecular weight of the polylactic acid block is 50000, 60000, 80000, 100000, 120000, etc. The number average molecular weight of the polylactic acid block meets the given conditions, which can form a suitable amount of porous structure, reduce the dielectric constant, and improve the mechanical and thermal properties.
[0071] In some embodiments, the insulating film satisfies at least one of the following conditions: under an electromagnetic wave frequency of 1 kHz, the dielectric constant of the insulating film is 2.01 to 2.28, and the dielectric loss factor is 0.001 to 0.006; the tensile strength of the insulating film is 180 MPa to 222 MPa; the elongation at break of the insulating film is 190.4% to 211.2%; the thermal expansion coefficient of the insulating film is 60.02 ppm / °C to 71.23 ppm / °C.
[0072] For example, under an electromagnetic wave frequency of 1kHz, the dielectric constant of the insulating film can be 2.05, 2.08, 2.10, 2.12, 2.15, 2.18, 2.20, 2.22, 2.25, etc., and the dielectric loss factor can be 0.002, 0.003, 0.004, 0.005, etc. The dielectric constant and dielectric loss factor meet the given conditions, which can improve the PDIV value of the enameled wire and avoid insulation loss due to partial discharge. At the same time, it can also reduce energy loss, reduce heat generation, improve insulation performance, reduce electric field concentration, increase signal transmission speed, and reduce electromagnetic interference.
[0073] Exemplarily, the tensile strength of the insulating film may be 185 MPa, 190 MPa, 195 MPa, 200 MPa, 205 MPa, 210 MPa, 215 MPa, 220 MPa, etc. The tensile strength satisfies the given conditions, the insulating film has good mechanical properties, can withstand certain mechanical stress and tension, is not easy to break and damage, is not easy to crack or deform during processing operations such as cutting and forming, has good impact resistance, and has a long service life.
[0074] For example, the elongation at break of the insulating film may be 193%, 195%, 198%, 200%, 202%, 205%, 208%, 210%, etc. The elongation at break satisfies the given conditions, and the insulating film can withstand large deformation without breaking when stretched or stressed, thereby improving the durability, impact resistance, and structural stability of the insulating film.
[0075] Exemplarily, the thermal expansion coefficient of the insulating film is 62ppm / °C, 64ppm / °C, 65ppm / °C, 68ppm / °C, 70ppm / °C, etc. The thermal expansion coefficient meets the given conditions, the insulating film has a small dimensional change under temperature changes, is dimensionally stable, reduces thermal deformation, and reduces thermal stress to reduce the risk of material delamination or fracture.
[0076] The second aspect of the present application provides a method for preparing the insulating film of the first aspect of the present application, the method comprising: subjecting an insulating base film to degradation treatment to obtain the insulating film having a porous structure;
[0077] The insulating base film includes a second block polymer, the second block polymer includes the polyimide block and the polylactic acid block, and the content of the polylactic acid block in the insulating base film is greater than the content of the polylactic acid block in the insulating film.
[0078] The insulating base film contains polylactic acid, which will produce CO2 during the degradation process to form a porous structure. The porous structure can be connected to the air, further reducing the dielectric constant of the insulating film. In addition, due to the consumption of polylactic acid, the polylactic acid block content in the insulating film is lower than the polylactic acid block content in the insulating base film. Therefore, the insulating film prepared by the method of the present application has low dielectric properties and excellent mechanical and thermal properties, and the preparation method is simple to operate, low in cost, and suitable for industrial applications. The characteristics and advantages described for the insulating film in the first aspect are also applicable to this method and will not be repeated here.
[0079] It should be noted that the types and characteristics of the polyimide blocks and polylactic acid blocks described in the insulating film of the first aspect are the same as the types and characteristics of the polyimide blocks and polylactic acid blocks in the insulating base film, and will not be repeated here.
[0080] In some embodiments, the molar ratio of the polyimide block to the polylactic acid block in the second block polymer is 1:(2-2.5). Exemplarily, the molar ratio of the polyimide block to the polylactic acid block in the second block polymer is 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, etc. Thus, the insulating film can further have low dielectric properties and excellent mechanical and thermal properties, is not easy to become brittle, and is easy to form a film.
[0081] In some embodiments, see Figure 1 The method for preparing the second block polymer includes: S100 polymerization treatment, S200 esterification treatment and S300 imidization treatment. Each step will be described in detail below.
[0082] S100 Aggregation Processing
[0083] In this step, the diamine monomer and the dianhydride monomer are polymerized in an organic solvent to obtain a polymerized slurry. The diamine monomer and the dianhydride monomer react to generate polyamic acid.
[0084] In some embodiments, the organic solvent includes at least one of N,N-dimethylacetamide, N-methylpyrrolidone, m-cresol, and 1,4-butyrolactone. The diamine monomer and the dianhydride monomer can be dissolved in the organic solvent under given conditions and the polymerization process efficiency and yield are high.
[0085] In some embodiments, the polymerization treatment temperature is 25° C. to 30° C. Exemplarily, the polymerization treatment temperature is 26° C., 27° C., 28° C., 29° C., etc. Thus, the polymerization reaction efficiency and yield can be further improved.
[0086] In some embodiments, the polymerization treatment time is 8 hours to 10 hours. Exemplarily, the polymerization treatment time is 8.5 hours, 9 hours, 9.5 hours, etc. Thus, the polymerization reaction can be completed efficiently in a short time with a high product yield.
[0087] In some embodiments, the viscosity of the polymer slurry is 90000cps to 110000cps. Exemplarily, the viscosity of the polymer slurry is 92000cps, 95000cps, 98000cps, 100000cps, 105000cps, etc. The viscosity of the polymer slurry meets the given conditions, has good coating performance, is easy to form a uniform film, has good surface quality and internal structure of the film, and has excellent mechanical and thermal properties.
[0088] S200 esterification treatment
[0089] In this step, the polymerized slurry is subjected to esterification treatment with polylactic acid to obtain an esterified product. The hydroxyl groups in the polyamic acid react with the carboxyl groups in the polylactic acid to form ester bonds.
[0090] In some embodiments, see Figure 2 , the esterification treatment comprises:
[0091] S210 Hybrid
[0092] In this step, the polymerization slurry, the catalyst and the slurry containing polylactic acid are mixed to obtain a mixed solution.
[0093] In some embodiments, the catalyst includes one or more of 4-dimethylaminopyridine (DMAP), pyridine, triethylamine, and N-methylpiperidine. Thus, the reaction efficiency is high and the product yield is high.
[0094] In some embodiments, the dehydrating agent includes one or more of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) and N,N-dicyclohexylcarbodiimide (DCC). Thus, water can be removed efficiently, and the yield and purity of the product can be improved.
[0095] In some embodiments, the solvent contained in the dehydrating agent solution includes: one or more of N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), m-cresol, 1,4-butyrolactone (GBL), preferably DMAc and / or NMP. Thus, the reactants have good solubility, high reaction efficiency, and high product purity and yield.
[0096] S220 Activation
[0097] In this step, the dehydrating agent solution is dripped into the mixed solution to perform an activation reaction to obtain an activation solution, thereby helping to improve the reaction success rate, reaction rate and reaction yield.
[0098] In some embodiments, the temperature of the activation reaction is -2°C to 2°C. Exemplarily, the temperature of the activation reaction is -2°C, -1°C, 0°C, 1°C, 2°C, etc. Thus, the activation reaction efficiency is high.
[0099] In some embodiments, the activation reaction time is 20 min to 40 min. Exemplarily, the activation reaction time is 25 min, 30 min, 35 min, etc. Thus, the activation reaction efficiency is high.
[0100] S230 Esterification
[0101] In this step, the activation solution is subjected to an esterification reaction to obtain an esterified product. The hydroxyl group reacts with the carboxyl group in the polylactic acid to form an ester bond.
[0102] In some embodiments, the temperature of the esterification reaction is 25° C. to 30° C. Exemplarily, the temperature of the esterification reaction is 26° C., 27° C., 28° C., 29° C., etc. Thus, the esterification efficiency is high, and the product purity and yield are high.
[0103] In some embodiments, the esterification reaction time is 8 hours to 15 hours. For example, the esterification reaction time is 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, etc. Thus, the esterification efficiency is high, and the product purity and yield are high.
[0104] S300 imidization treatment
[0105] In this step, the esterification product is imidized to obtain the second block polymer. The amic acid in the esterification product is cyclized and dehydrated to form polyimide, and finally the second block polymer is obtained.
[0106] In some embodiments, the imidization treatment includes: 70°C to 90°C (for example, 75°C, 80°C, 85°C, etc.) for 40min to 60min (for example, 45min, 50min, 55min, etc.), 150°C to 170°C (for example, 155°C, 160°C, 165°C, etc.) for 20min to 40min (for example, 25min, 30min, 35min, etc.), 240°C to 260°C (for example, 245°C, 250°C, 255°C, etc.) for 20min to 40min (for example, 25min, 30min, 35min, etc.). Thus, block polymers can be prepared efficiently with high product yield and purity.
[0107] In some embodiments, the imidization treatment time is 20 min to 60 min. Exemplarily, the imidization treatment time is 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, etc. Thus, the block polymer can be prepared efficiently with high product yield and purity.
[0108] In some embodiments, the degradation treatment includes placing the insulating base film at a temperature of 20° C. to 30° C. for 10 to 30 days. Thus, a porous structure satisfying the given conditions can be formed, and the dielectric constant of the insulating film can be reduced.
[0109] The third aspect of the present application provides an enameled wire, the enameled wire comprising: a conductor; the insulating film of the first aspect of the present application, the insulating film covering the outer peripheral surface of the conductor. The enameled wire according to the present application has an excellent partial discharge starting voltage value, high insulation performance, can avoid partial discharge phenomenon under high voltage, maintain stable operation, and has a long service life.
[0110] The fourth aspect of the present application provides a motor, the motor comprising: the enameled wire described in the third aspect of the present application. According to the motor of the present application, by applying the enameled wire, the partial discharge starting voltage value can be increased, the insulation is high, thereby improving the stability and working efficiency of the motor operation, extending the service life, and meeting different rated voltage requirements.
[0111] In some embodiments, the rated voltage of the motor is not less than 800 V. The enameled wire according to the present application can be used for the above high rated voltage.
[0112] The fifth aspect of the present application proposes a vehicle, which includes: the motor described in the fourth aspect of the present application. According to the vehicle of the present application, by applying the above motor, the vehicle has at least the following advantages: it is easier to achieve high power and high torque, so that the vehicle has good acceleration and a wide range of high efficiency areas; the working current is small under the same power, reducing line losses; it can be compatible with high and low voltage platforms to achieve product serialization; the charging speed is fast, and fast charging is easier to achieve.
[0113] It should be noted that the features and advantages described above for the insulating film are also applicable to the enameled wire, motor and vehicle, and will not be elaborated here.
[0114] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.
[0115] Example 1
[0116] (1) 3,3'-dihydroxybenzidine (0.1 mol, 21.62 g) and 6FDA (0.105 mol, 46.64 g) were added to DMAc (273 g, 20% solid content) and reacted at 25°C for 10 h until the solution was completely dissolved to obtain PI slurry (M n =125864, viscosity is 104587cps;
[0117] (2) The PI slurry (2 g, 0.58 mmol) and PLA slurry (M n =60000, 70.33g, 1.172mmol), DMAP (0.035g, 0.29mmol) were dissolved in a round-bottom flask, EDC (0.018g, 0.116mmol) was dissolved in 10mL-15mL DMAc, and the EDC solution was slowly dripped into the reaction system under ice bath conditions. After activation reaction under ice bath conditions for 30min, the reaction was moved to room temperature. After esterification for 8h, the PI-PLA esterification product was obtained, and the molar ratio of polyimide block to polylactic acid block was 1:2;
[0118] (3) thermally imidizing the PI-PLA esterification product obtained in step (2), coating it on a glass plate, and curing it at 80° C. for 50 min; 160° C. for 30 min; and 250° C. for 30 min in sequence to prepare a 25 μm film, wherein the molar ratio of the polyimide block to the polylactic acid block is 1:2;
[0119] (4) The PI-PLA film prepared in step (3) is placed in air for 10 days to obtain an insulating film with a porous structure.
[0120] Example 2
[0121] (1) Same as step (1) of Example 1;
[0122] (2) The PI slurry (2 g, 0.58 mmol) and PLA slurry (M n =80000, 93.76g, 1.172mmol), DMAP (0.035g, 0.29mmol) were dissolved in a round-bottom flask, EDC (0.018g, 0.116mmol) was dissolved in 10mL-15mL DMAc, and the EDC solution was slowly dripped into the reaction system under ice bath conditions. After activation reaction under ice bath conditions for 30min, the reaction was moved to room temperature. After esterification for 12h, the PI-PLA esterification product was obtained, and the molar ratio of polyimide block to polylactic acid block was 1:2;
[0123] (3) Same as step (3) of Example 1;
[0124] (4) The PI-PLA film prepared in step (3) is placed in air for 10 days to obtain an insulating film with a porous structure.
[0125] Example 3
[0126] (1) Same as step (1) of Example 1;
[0127] (2) The PI slurry (2 g, 0.58 mmol) and PLA slurry (M n =110000, 128.92g, 1.172mmol), DMAP (0.035g, 0.29mmol) were dissolved in a round-bottom flask, EDC (0.018g, 0.116mmol) was dissolved in 10mL-15mL DMAc, and the EDC solution was slowly dripped into the reaction system under ice bath conditions. After activation reaction under ice bath conditions for 30min, the reaction was moved to room temperature. After esterification for 15h, the PI-PLA esterification product was obtained, and the molar ratio of polyimide block to polylactic acid block was 1:2;
[0128] (3) Same as step (3) of Example 1;
[0129] (4) The PI-PLA film prepared in step (3) is placed in air for 10 days to obtain an insulating film with a porous structure.
[0130] Example 4
[0131] (1) 3,3'-dihydroxybenzidine (0.1 mol, 21.62 g) and 6FDA (0.105 mol, 46.64 g) were added to DMAc (159 g, 30% solid content) and reacted at 25°C for 10 h until the solution was completely dissolved to obtain PI slurry (M n =184597, viscosity is 104587cps;
[0132] (2) The PI slurry (2 g, 0.881 mmol) and PLA slurry (M n =60000, 105.66g, 1.761mol), DMAP (0.0538g, 0.0441mmol) were dissolved in a round-bottom flask, EDC (0.0274g, 0.1762mmol) was dissolved in 10mL-15mL DMAc, and the EDC solution was slowly dripped into the reaction system under ice bath conditions. After activation reaction under ice bath conditions for 30min, the reaction was moved to room temperature. After esterification for 8h, the PI-PLA esterification product was obtained, and the molar ratio of polyimide block to polylactic acid block was 1:2;
[0133] (3) Same as step (3) of Example 1;
[0134] (4) The PI-PLA film prepared in step (3) is placed in air for 10 days to obtain an insulating film with a porous structure.
[0135] Example 5
[0136] (1) 3,3'-dihydroxybenzidine (0.1 mol, 21.62 g) and 6FDA (0.105 mol, 46.64 g) were added to DMAc (614 g, 10% solid content) and reacted at 25°C for 10 h until the solution was completely dissolved to obtain PI slurry (M n =108123, viscosity is 104587cps;
[0137] (2) The PI slurry (2 g, 2.930 mmol) and PLA slurry (M n=60000, 35.16g, 0.586mmol), DMAP (0.178g, 1.465mmol) were dissolved in a round-bottom flask, EDC (0.091g, 0.586mmol) was dissolved in 10mL-15mL DMAc, and the EDC solution was slowly dripped into the reaction system under ice bath conditions. After activation reaction under ice bath conditions for 30min, the reaction was moved to room temperature. After esterification for 8h, the PI-PLA esterification product was obtained, and the molar ratio of polyimide block to polylactic acid block was 1:2;
[0138] (3) Same as step (3) of Example 1;
[0139] (4) The PI-PLA film prepared in step (3) is placed in air for 10 days to obtain an insulating film with a porous structure.
[0140] Example 6
[0141] (1) 3,3'-dihydroxybenzidine (0.1 mol, 21.62 g) and 6FCDA (0.105 mol, 46.64 g) were added to DMAc (273 g, 20% solid content) and reacted at 25°C for 10 h until the solution was completely dissolved to obtain PI slurry (M n =152347, viscosity is 104587cps);
[0142] (2) The same as step (2) of Example 1, to obtain a PI-PLA esterification product, wherein the molar ratio of the polyimide block to the polylactic acid block is 1:2;
[0143] (3) Same as step (3) of Example 1;
[0144] (4) The PI-PLA film prepared in step (3) is placed in air for 10 days to obtain an insulating film with a porous structure.
[0145] Example 7
[0146] (1) Same as step (1) of Example 1;
[0147] (2) Same as step (2) of Example 1;
[0148] (3) Same as step (3) of Example 1;
[0149] (4) The PI-PLA film prepared in step (3) is placed in air for 20 days to obtain an insulating film with a porous structure.
[0150] Example 8
[0151] (1) Same as step (1) of Example 1;
[0152] (2) Same as step (2) of Example 1;
[0153] (3) Same as step (3) of Example 1;
[0154] (4) The PI-PLA film prepared in step (3) is placed in air for 30 days to obtain an insulating film with a porous structure.
[0155] Example 9
[0156] (1) Same as step (1) of Example 1;
[0157] (2) Same as step (2) of Example 1;
[0158] (3) Same as step (3) of Example 1;
[0159] (4) The PI-PLA film prepared in step (3) is placed in air for 40 days to obtain an insulating film with a porous structure.
[0160] Example 10
[0161] (1) Same as step (1) of Example 1;
[0162] (2) The PI slurry (2 g, 0.58 mmol) and PLA slurry (M n =60000, 87.6g, 1.46mmol), DMAP (0.035g, 0.29mmol) were dissolved in a round-bottom flask, EDC (0.018g, 0.116mmol) was dissolved in 10mL-15mL DMAc, and the EDC solution was slowly dripped into the reaction system under ice bath conditions. After activation reaction under ice bath conditions for 30min, the reaction was moved to room temperature. After esterification for 8h, the PI-PLA esterification product was obtained, in which the molar ratio of polyimide block to polylactic acid block was 1:2.5;
[0163] (3) Same as step (3) of Example 1;
[0164] (4) The PI-PLA film prepared in step (3) is placed in air for 10 days to obtain an insulating film with a porous structure.
[0165] Embodiment 11
[0166] (1) Same as step (1) of Example 1;
[0167] (2) The PI slurry (2 g, 0.58 mmol) and PLA slurry (M n=60000, 35.164g, 0.586mmol), DMAP (0.035g, 0.29mmol) were dissolved in a round-bottom flask, EDC (0.018g, 0.116mmol) was dissolved in 10mL-15mL DMAc, and the EDC solution was slowly dripped into the reaction system under ice bath conditions. After activation reaction under ice bath conditions for 30min, the reaction was moved to room temperature. After esterification for 8h, the PI-PLA esterification product was obtained, and the molar ratio of polyimide block to polylactic acid block was 1:1;
[0168] (3) Same as step (3) of Example 1;
[0169] (4) The PI-PLA film prepared in step (3) is placed in air for 30 days to obtain an insulating film with a porous structure.
[0170] Example 12
[0171] The difference between Example 13 and Example 1 is that 6FDA is replaced by pyromellitic dianhydride (PMDA).
[0172] Comparative Example 1
[0173] The difference between Comparative Example 1 and Example 1 is that step (2) is not included, and the PI slurry prepared in step (1) is directly subjected to steps (3) and (4).
[0174] Comparative Example 2
[0175] Purchased PLA (Mn=60000) was cast into a film and left in air for 10 days to obtain an insulating film.
[0176] Test Case
[0177] The insulating films prepared in Examples 1 to 12 and Comparative Examples 1 to 2 were respectively tested for composition, mechanical, thermal and dielectric properties, including dielectric constant (Dk), dielectric loss (Df), tensile strength, elongation at break, and coefficient of thermal expansion (CTE). The test methods are as follows:
[0178] Composition test: Tested according to JY / T 003-1996 General Rules for Organic Mass Spectrometry Analysis.
[0179] Porosity test method: Using the solvent immersion method, first weigh the weight m of the insulating film, and calculate the volume of the film based on the density of the polymer, which is recorded as V1; the insulating film is placed in 10mL of deionized water at room temperature for 30 minutes and then taken out, and the volume of the remaining water is measured. The reduced water volume is recorded as V2, and the porosity / % = V2×100% / (V1+V2).
[0180] Tensile strength and elongation at break: tested according to GB / T 1040.3-2006.
[0181] Thermal expansion coefficient: measured using Mettler static thermomechanical tester TMA / SDTA 2+ in a measuring temperature range of 50-200°C and a heating rate of 10°C / min.
[0182] Dielectric constant and dielectric loss: tested according to GB / T31838.6-2021.
[0183] The results are shown in Table 1. The performance of the insulating films prepared in Examples 1 to 12 is better than that of the insulating films prepared in Comparative Examples 1 to 2. In Comparative Example 1, the polyimide cannot form a porous structure after being placed in the air, resulting in a high dielectric constant, a low thermal expansion coefficient, poor heat dissipation performance and an unstable structure. In Comparative Example 2, only polylactic acid is used as the insulating film composition, which will result in low tensile strength and elongation at break of the insulating film, and poor dynamic performance. In addition, the thermal expansion coefficient is high, and it is easy to crack or delaminate under large temperature differences.
[0184] Table 1
[0185]
[0186] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0187] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. An insulating film, It is characterized in that The insulating film includes a block polymer, and the block polymer includes: a polyimide block and a polylactic acid block; The insulating film has a porous structure.
2. The insulating film according to claim 1, It is characterized in that The porosity of the porous structure is 20% to 80%.
3. The insulating film according to claim 1, It is characterized in that The polyimide block is generated by reacting at least a dianhydride monomer and a diamine monomer; Optionally, the diamine monomer has a hydroxyl group, which can undergo an esterification reaction with a carboxyl group in the polylactic acid block.
4. The insulating film according to claim 3, It is characterized in that The dianhydride monomer further has a fluorine group; And / or, the dianhydride monomer includes at least one of hexafluoroisopropylphthalic anhydride, 9,9-bis(trifluoromethyl)-2,3,6,7-oxanthene tetracarboxylic dianhydride, 1,4-bis(3,4-dicarboxytrifluorophenoxy)tetrafluorophthalic anhydride, 1,4-bis(trifluoromethyl)-2,3,5,6-benzenetetracarboxylic dianhydride, 1,4-difluoropyromellitic dianhydride, and 2,2-bis[4-(3,4-dicarboxytrifluorophenoxy)phenyl]hexafluoropropane dianhydride; And / or, the diamine monomer includes at least one of 3,3'-dihydroxybenzidine, 4,6-diaminoresorcinol dihydrochloride and 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane.
5. The insulating film according to claim 1, It is characterized in that The number average molecular weight of the polyimide block is 105000 to 200000; And / or, the number average molecular weight of the polylactic acid block is 50,000 to 120,000.
6. The insulating film according to claim 1, It is characterized in that The insulating film satisfies at least one of the following conditions: Under an electromagnetic wave with a frequency of 1 kHz, the dielectric constant of the insulating film is 2.01 to 2.28, and the dielectric loss factor is 0.001 to 0.006; The tensile strength of the insulating film is 180MPa to 222MPa; The elongation at break of the insulating film is 190.4% to 211.2%; The thermal expansion coefficient of the insulating film is 60.02 ppm / °C to 71.23 ppm / °C.
7. A method for preparing the insulating film according to any one of claims 1 to 6, It is characterized in that include: Degrading the insulating base film to obtain the insulating film having a porous structure; The insulating base film includes a second block polymer, the second block polymer includes the polyimide block and the polylactic acid block, and the content of the polylactic acid block in the insulating base film is greater than the content of the polylactic acid block in the insulating film.
8. The method according to claim 7, It is characterized in that The molar ratio of the polyimide block to the polylactic acid block in the second block polymer is 1:(2-2.5).
9. The method according to claim 7, It is characterized in that The method for preparing the second block polymer comprises: The diamine monomer and the dianhydride monomer are polymerized in an organic solvent to obtain a polymerization slurry; Esterifying the polymerized slurry with polylactic acid to obtain an esterified product; The esterification product is subjected to imidization treatment to obtain the second block polymer.
10. The method according to claim 9, It is characterized in that The organic solvent comprises: at least one of N,N-dimethylacetamide, N-methylpyrrolidone, m-cresol, and 1,4-butyrolactone; And / or, the polymerization treatment temperature is 25°C to 30°C; And / or, the polymerization treatment time is 8h to 10h; And / or, the viscosity of the polymerization slurry is 90,000 cps to 110,000 cps.
11. The method according to claim 9 or 10, It is characterized in that The esterification treatment comprises: The polymerization slurry, the catalyst and the slurry containing polylactic acid are mixed to obtain a mixed solution; Dropping a dehydrating agent solution into the mixed solution to perform an activation reaction to obtain an activated solution; The activation solution is subjected to an esterification reaction to obtain the esterification product.
12. The method according to claim 11, It is characterized in that The catalyst comprises one or more of 4-dimethylaminopyridine, pyridine, triethylamine and N-methylpiperidine; And / or, the dehydrating agent comprises: one or more of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N,N-dicyclohexylcarbodiimide; And / or, the solvent contained in the dehydrating agent solution includes: one or more of N,N-dimethylacetamide, N-methylpyrrolidone, m-cresol, and 1,4-butyrolactone; And / or, the temperature of the activation reaction is -2°C to 2°C; And / or, the activation reaction time is 20min to 40min; And / or, the temperature of the esterification reaction is 25°C to 30°C; And / or, the esterification reaction time is 8h to 15h.
13. The method according to claim 9, It is characterized in that The imidization treatment includes: 70° C. to 90° C. for 40 min to 60 min, 150° C. to 170° C. for 20 min to 40 min, and 240° C. to 260° C. for 20 min to 40 min.
14. The method according to claim 7, It is characterized in that The degradation treatment includes placing the insulating base film at a temperature of 20° C. to 30° C. for 10 days to 30 days.
15. An enameled wire, It is characterized in that include: conductor; The insulating film according to any one of claims 1 to 6, wherein the insulating film covers the outer peripheral surface of the conductor.
16. A motor, It is characterized in that include: The enameled wire according to claim 15.
17. The electric machine according to claim 16, It is characterized in that The rated voltage of the motor is not less than 800V.
18. A vehicle, It is characterized in that include: A motor as claimed in claim 16 or 17.
Citation Information
Patent Citations
Method for preparing polyimide porous diaphragm
CN109473605A
Polyimide-polyester copolymer and preparation and application thereof
CN115785417A
Spiral twenty-four-surface structure nano-porous polyimide film and preparation method thereof
CN116903920A
High-temperature-resistant polyimide enameled wire and preparation method thereof
CN116913585A
Mesoporous polyimide thin films as dendrite-suppressing separators for alkali metal batteries
WO2023220458A1
